PENERAPAN MODEL UTAUT 2 TERHADAP NIAT PENGGUNAAN ELECTRONIC PAYMENT SHOPEEPAY DI KOTA SEMARANG - Fani Audriyani; Wahyu Meiranto (Diponegoro Journal of Accounting, 2023)
This study aims to analyze several factors that influence behavioral intentions to use ShopeePay in Semarang. The study was carried out using the Unified Theory of Acceptance and Use of Technology (UTAUT) 2 model proposed by Venkatesh et al. (2012). The UTAUT 2 model is comprised of seven factors, namely performance expectancy, effort expectancy, social influence, facilitating conditions, habits, hedonic motivation, and behavioral intentions to use ShopeePay. The research population consisted of active ShopeePay users in Semarang, with 100 respondents serving as a sample for testing the research model. The data was collected using an online questionnaire-assisted survey with 25 questions and analyzed using the PLS-SEM method in the SmartPLS 3 software. The findings confirmed that the four hypotheses were accepted. Performance expectancy, social influence, habits, and hedonic motivation had a significant positive effect on behavioral intention to use ShopeePay. In the meantime, effort expectancy and facilitating conditions had no effect on behavioral intentions. Furthermore, it is known that habit is the strongest predictor of behavioral intention to use ShopeePay.